If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t * t + 9 = 6t Multiply t * t t2 + 9 = 6t Reorder the terms: 9 + t2 = 6t Solving 9 + t2 = 6t Solving for variable 't'. Reorder the terms: 9 + -6t + t2 = 6t + -6t Combine like terms: 6t + -6t = 0 9 + -6t + t2 = 0 Factor a trinomial. (3 + -1t)(3 + -1t) = 0Subproblem 1
Set the factor '(3 + -1t)' equal to zero and attempt to solve: Simplifying 3 + -1t = 0 Solving 3 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1t = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1t = 0 + -3 -1t = 0 + -3 Combine like terms: 0 + -3 = -3 -1t = -3 Divide each side by '-1'. t = 3 Simplifying t = 3Subproblem 2
Set the factor '(3 + -1t)' equal to zero and attempt to solve: Simplifying 3 + -1t = 0 Solving 3 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1t = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1t = 0 + -3 -1t = 0 + -3 Combine like terms: 0 + -3 = -3 -1t = -3 Divide each side by '-1'. t = 3 Simplifying t = 3Solution
t = {3, 3}
| -2w-11=11 | | a*a+40a=0 | | -4y-2(-2y-7)=9+2(-1-y) | | r*r-4r=0 | | 7d=-35 | | -4y+(4y+14)=9+(-2-2y) | | (3t-15)(4r+22)= | | 5x-12=2x | | 156-123.5=x | | p^2-169q^2= | | 2x=247 | | m+16-2m+3m=4m-23+16 | | ln(x+4)+ln(x)=ln(x+18) | | (2k+6)=(k+5k-1) | | 28y+13=25y+6 | | 3x^3-4x-52=0 | | tn=2n-5 | | 2x+10x-10+3=450 | | 2x+10-5=205 | | 3y-14=x | | 3b+c^2=5 | | x-x^2+2=0 | | 7x-14=49 | | -6x^2=2x+(73-x+4)-2 | | (2a-1)(a-5)= | | 45-5x=4x+16 | | 5-10x=85-24x | | 52-5x=13x+24 | | 210-2x=34x+18 | | 2k-6=3k+5 | | 9-10x=194-45x | | x=65*x^2-3x |